The Effectiveness of Gymnastic Respiratory Muscle Stretch and Buteyko Breathing Exercise on Peak Expiratory Flows in Older Population - Mahfud Hidayat; Ali Multazam (Physical Therapy Journal of Indonesia, 2020)
Introduction: Elderly is a period of life characterized by changes in function and a decrease in social life so that result in changes in muscle tissue including the respiratory system. Respiratory function in older population will decrease due to age and caused many problems. The purpose of this study was to find out the combination of respiratory muscles stretch gymnastic with buteyko breathing exercises to increase the peak expiratory flow in the elderly. Methods: The study design is an analytical experimental method with quasi-experimental pre-test and post-test two groups design, the population in the study in Sumbersekar Village that met the inclusion criteria for three weeks. Sample in this study is 56 samples divided into experimental group and control group. Experiment group consisted of 30 samples and the control group consisted of 26 samples. Research data were analyzed by Wilcoxon Signed Rank Test. Results: The results of this study before and after intervention are p = 0,000 and H1 accept. The interpretation of this results is there is an effect of the combination of gymnastic respiratory muscle stretch with buteyko breathing exercises in older population. Conclusion: There is an effect of gymnastic respiratory muscle stretch with buteyko breathing exercise in older population.